PROFITABILITAS PENGARUH KECUKUPAN MODAL, PENYALURAN PEMBIAYAAN, TINGKAT PEMBIAYAAN BERMASALAH TERHADAP PROFITABILITAS PADA PERBANKAN SYARIAH PERIODE 2018 – 2022: PENGARUH KECUKUPAN MODAL, PENYALURAN PEMBIAYAAN, TINGKAT PEMBIAYAAN BERMASALAH TERHADAP PROFITABILITAS PADA PERBANKAN SYARIAH PERIODE 2018 – 2022 - Anggita, Arum - (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study was conducted to determine the effect of capital adequacy, financing distribution and the level of non-performing financing on profitability in Islamic banking for the period 2018 - 2022. Data obtained from the financial statements of Islamic Commercial Banks in Indonesia. The method used in the research is descriptive statistics and the variables used are capital adequacy, financing distribution and level of non-performing financing. The data analysis used is panel data regression analysis. The results showed that the variables of capital adequacy and financing distribution had a positive effect on profitability in Islamic banking, while the level of non-performing financing had a negative effect on profitability in Islamic banking.